Signifikansi Dialog Antaragama Dalam Era Post-Fundamentalisme - Sholahuddin - (Millah: Journal of Religious Studies, 2004)
After September eleven, the face of Islam in the global world was dominated by the fundamentalism. Here, the effect of the accident not only felt by the Osama bin Laden who became the number one public enemy, but also Islam get trickle effect from this accident. In this paper, the writer elaborates the significance of interreligious dialogue based on the dialogue of civilization. In the multicultural era one method or way to minimize the prejudices that exist under the consciousness of people is through dialogue, whether interreligious and interfaith dialogue, or dialogue of civilization. However, the dialogue in this paper should be understood in the state of becoming and going on process. This process is based on particular doctrine to common plat form (kalimah sawa'). This article gives some review from Islamic perspective. Of course, these values support religious and inter-faith dialogue, or what the writer called "blueprint" of dialogue.